Prevalence of tinnitus according to temporomandibular joint disorders and dental pain: The Korean National Population‐based Study. (21st January 2018) - Kim, Y. H.; Park, Y. G.; Han, K. D.; Vu, D.; Cho, K. H.; Lee, S. Y.
Summary: Some studies have reported that temporomandibular joint disorder (TMD) is related to tinnitus. However, there is no study of the relationship and prevalence of dental pain and tinnitus. We evaluated the associations between the prevalence of tinnitus and TMD and dental pain by analysing the Korean national health survey. We analysed totally 11 745 participants. The presence of tinnitus, TMD symptoms and dental pain was surveyed by self‐assessment questionnaires from all the participants. Multivariable regression analysis was applied to acquire odds ratios (OR) and 95% confidence intervals (CI). The prevalence of tinnitus was higher in the subjects with dental pain (21.1%), TMD (22.5%) and both symptoms (31.2%) than subjects without those symptoms (19.6%). After adjusting for all covariates, subjects with TMD had tinnitus 1.6 times more than subjects without TMD. In the subanalysis, age group more than 65 years, women, and obese subjects had tinnitus more than men, age group <65, and non‐obese subjects, respectively. TMD alone and both dental pain and TMD were associated with tinnitus (OR = 1.389 and 95% CI 1.054‐1.832 and 2.206 and 1.637‐2.974, respectively). Subjects with TMD had more tinnitus than subjects without TMD. Moreover, subjects with dental pain in addition to TMD had increased prevalence of tinnitus than TMD alone.